Self-medication for prevention and treatment of COVID-19 like illness in Nampula City, Mozambique - Afai, Gerson; Gelane, Abacar; Banze, Auria Ribeiro; Rossetto, Erika Valeska (InterAmerican Journal of Medicine and Health, 2024)
Medicines are an essential part of healthcare for maintaining life, but the lack of knowledge about the self-medication risks, and the health facility wait time can influence self-medication. As part of the coronavirus disease 2019 (COVID-19) surveillance efforts, we used a semi-structured questionnaire of closed questions to conducted interviews in five pharmacies in Nampula City about self-medication increase, in June 2020, during the emergency of COVID-19. From March to June 2020, most of interviewed pharmacies (3/5) verified an increase in self-medication. The most common medicines bought by the costumers were anti-flu (4/5) and antibiotics (3/5). People who self-medicated reported flu-like-symptoms (5/5) and cough (4/5). We recommend pharmacies to refer people who were seeking to self-medicate and who presented COVID-19-like signs and symptoms to the health facility for testing.